2014
DOI: 10.1007/s13659-014-0024-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Artemisinin Against Cancer Cell Lines

Abstract: The present study aims at defining the differential cytotoxicity effect of artemisinin toward P815 (murin mastocytoma) and BSR (kidney adenocarcinoma of hamster) cell lines. Cytotoxicity was measured by the growth inhibition using MTT assay. These in vitro cytotoxicity studies were complemented by the determination of apoptotic DNA fragmentation and Annexin V- streptavidin-FITC assay. Furthermore, we examined the in vitro synergism between artemisinin and the chemotherapeutic drug, vincristin. The in vivo stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 26 publications
(33 reference statements)
5
42
0
Order By: Relevance
“…Cyclin A, CDK2 and CDC25A are critical factors associated with the S phase of the cell cycle (35). CDC25A may activate CDK2, which in turn leads to the activation of the cyclin-CDK complex and causes cell cycle progression (36,37). The present study demonstrated that CQ reduced the expression of CDC25A and CDK2, and increased the expression of cyclin A.…”
Section: Discussionsupporting
confidence: 51%
“…Cyclin A, CDK2 and CDC25A are critical factors associated with the S phase of the cell cycle (35). CDC25A may activate CDK2, which in turn leads to the activation of the cyclin-CDK complex and causes cell cycle progression (36,37). The present study demonstrated that CQ reduced the expression of CDC25A and CDK2, and increased the expression of cyclin A.…”
Section: Discussionsupporting
confidence: 51%
“…CDC25A is activated by cyclin A/CDK2 complexes. These complexes allow for progression of the cell cycle, and increased expression of CDC25A promotes cell growth (57,58). We have demonstrated that treatment with the C. soldanella 85% aq.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study from our laboratory demonstrated that artemisinin has a differential effect on cancer cells. In fact, Artemisinin induced lysis on the murin mastocytoma cancer cell line (P815) with IC 50 = 12 μM and on Kidney adeno‐carcinoma cell line of hamsters with IC 50 = 52 μM (Tilaoui, Mouse, Jaafari, & Zyad, ). Furthermore, artemisinin was described to possess an anticancer effect on breast, lung, prostate, colon, leukemia, and other cancer cell types, as summarized in Table .…”
Section: In Vitro Anticancer Effectsmentioning
confidence: 99%
“…Artemisinin has been described to induce apoptosis effects (Chen, Li, Zhang, & Wang, ; Efferth, Giaisi, Merling, Krammer, Li‐Weber ; Hamacher‐Brady et al, ; Tilaoui et al, ; Zheng, Wang, Huang, Luo, & Mi, ), as well as cell cycle arrest, especially at G0/G1 cell cycle transition phase (Tin, Sundar, Tran, et al, ; Willoughby et al, ; Wu et al, ). Multiple lines of evidence suggest that the apoptotic pathway could be due to intra and/or extra‐mitochondrial mode of action and the involvements of iron/heme as well (Efferth et al, ; Lai & Singh, ; Singh & Lai, ; Zhang, Chen, & Gerhard, ).…”
Section: In Vitro Anticancer Effectsmentioning
confidence: 99%